The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4014/jmb.1104.04012
|View full text |Cite
|
Sign up to set email alerts
|

Rehmannia glutinosa Ameliorates Scopolamine-Induced Learning and Memory Impairment in Rats

Abstract: Many studies have shown that the steamed root of Rehmannia glutinosa (SRG), which is widely used in the treatment of various neurodegenerative diseases in the context of Korean traditional medicine, is effective for improving cognitive and memory impairments. The purpose of this study was to examine whether SRG extracts improved memory defects caused by administering scopolamine (SCO) into the brains of rats. The effects of SRG on the acetylcholinergic system and proinflammatory cytokines in the hippocampus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 31 publications
(39 reference statements)
1
35
0
1
Order By: Relevance
“…9,[40][41][42] The antioxidant properties of P. multiflorum water extract suppressed cognitive deficits induced by Aβ accumulation in mice. 9) We also found that P. multiflorum ethanol extract exerts neuroprotective effect and has antioxidant properties in both Drosophila and human cell AD models; this suggested that both water and ethanol extracts of P. multiflorum contains beneficial components for neuronal health, and that the neuroprotective mechanism of P. multiflorum extract may be conserved from fly to human.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[40][41][42] The antioxidant properties of P. multiflorum water extract suppressed cognitive deficits induced by Aβ accumulation in mice. 9) We also found that P. multiflorum ethanol extract exerts neuroprotective effect and has antioxidant properties in both Drosophila and human cell AD models; this suggested that both water and ethanol extracts of P. multiflorum contains beneficial components for neuronal health, and that the neuroprotective mechanism of P. multiflorum extract may be conserved from fly to human.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective effects of R. glutinosa have also been reported in several previous studies. 40,44,45) Moreover, catalpol, an iridoid glucoside isolated from the root of R. glutinosa, protected primary cultured cortical neurons from the Aβ42-induced damage, through a mitochondrial-dependent caspase pathway. 46) It is interesting to test whether catalpol also shows similar effect in our Drosophila models.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that LPS infusion into the lateral ventricle of rat brains retarded escape latency in the MWM test, indicating deficits in spatial learning ability and reference memory. The scoring of the escape latency from water in the spatial probe tests in the MWM test is primarily considered to reflect long-term spatial memory ability (Lee et al 2011). In this study, administration of PCE shortened the escape latency without affecting swimming velocity and extended the time spent swimming in the place where the platform was previously located.…”
Section: Discussionmentioning
confidence: 72%
“…The test was performed according to the step-through method described previously (Lee et al 2011). The Gemini Avoidance System (SD Instruments., San Diego, CA, USA) was used for this test.…”
Section: Passive Avoidance Testmentioning
confidence: 99%
See 1 more Smart Citation